An assessment of the provision of women-friendly care and its associated factors among mothers who gave birth at public health institutions in South Gondar Zone, Northwest Ethiopia - Ferede, Wassie Yazie; Berihun Erega, Besfat; Yehuala, Enyew Dagnew; Yimer, Tigist Seid (Frontiers in Global Women's Health, 2024)
Introduction “Women-friendly care” is one of the categories of respectful maternal care and is a method of providing care that improves women's access to safe parenting and to reproductive health services by creating a friendly environment at all levels. Improving service use is crucial, particularly in situations where it is low. There is limited data on women-friendly care during childbirth in Ethiopia. Objective This study aimed to assess the provision of women-friendly care and its associated factors among mothers who gave birth at health institutions in the South Gondar zone, Northwest Ethiopia. Methods A multicenter institutional-based cross-sectional study design was conducted among mothers who gave birth at South Gondar Zone public health institutions, from February 01 to March 30/2021. Three hundred forty-eight study participants were selected by using systematic random sampling. A validated questionnaire was used for data collection. For analysis, the data were imported into Epi-Data version 4.6 and exported to SPSS version 25. A multivariable logistic regression analysis was performed to identify factors associated with the outcome variable. An adjusted odds ratio with a 95% confidence interval was computed to determine the level of significance. Results The study had 344 participants in total, with a response rate of 98.85%. The study revealed that a full 73% [95%; CI: 68.6, 77.3%] its participants received women-friendly care. Having antenatal care follow-up [AOR: 3.02, 95% CI: 2.16–11.68], being a primipara [AOR = 2.30 95% CI: 1.23–5.49], not experiencing complications during childbirth [AOR: 2.13, 95% CI: 1.17–12.4], stays at health care facilities, specifically between 13 and 24 h [AOR: 0.25, 95% CI: 0.09–0.67], place for delivery [AOR: 2.01, 95% CI: 1.29–6.09] and delivering during daytime hours [AOR = 2.17, 95% CI: 1.08–5.65] were significantly associated with the provision of women-friendly care. Conclusions Only two-thirds of the study participants received Women's-friendly care during childbirth. It was found to be low in our study area in contrast with the majority of the previous findings. Our own findings also suggest the importance of minimizing elective induction of labor during night, of providing comprehensive counseling on antenatal care follow-up, of ensuring mothers remain at health care facilities until the recommended duration, and of implementing early prevention and management of childbirth complications to ensure that mothers receive women-friendly care.